THE ETHICAL ESSENCE OF THE CONCEPTS OF SHUKUR, RIDA AND SABR AS PER SUFI-PHILOSOPHICAL VIEWS OF AZIZIDDIN NASAFI (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In the following article the ethical essence of the concepts of shukur, rida and sabr as per sufi-philosophical views of Aziziddin Nasafi are reconsidered. His views are analysed from the viewpoint of the comparison of the treatises compiled by Khujviri based on his “Kashf al-Mahjub”.